450 Profile of self-inflicted harm in los angeles by race/ethnicity, 2001–2010. (1st September 2016) - Bazargan-Hejazi, S; Ahmadi, A; Rahmani, Elham; Mojtahedzadeh, M; Pan, D
Abstract : Background: Self-Inflicted Harm is one of the major causes of morbidity and mortality. Previous studies have shown that there are different patterns of SIH among different racial groups. This study aims to describe SIH admission rates and patterns among different racial groups in Los Angeles and to evaluate whether admission rates have changed over a ten year period (2001–2010). Methods: Data for this retrospective study includes all cases of hospital admission in Los Angeles with SIH based on the ICD-9:E950–E958 for 2001–2010. ICD-9 codes for schizophrenia, episodic mood disorders, depressive, anxiety, personality adjustment, sexual and gender identity disorders, as well as alcoholism and substance abuses were used. Results: A total of 2459 patients with SIH were identified. African Americans(AA) had the highest ten year average of SIH rate (11.6/100, 000) followed by Caucasians(CC) (8.44/100, 000), Latinos(LT) (6.21/100, 000) and Asians(AS) (1.64/100, 000). The SIH admission rates remained steady throughout the 10 year study period (P value = 0.3064) and none of the racial groups showed a significant change (P value CC = 0.2445, AA = 0.2120, LT = 0.6898, AS = 0.1237). Median age of SIH was significantly lower in Latinos (LT = 28 versus CC = 43, AA = 39 and AS = 40 (P value < 0.001). Overall, episodic mood disorders where the most common psychiatric comorbidity among all racial groups. However, AAs had the lowest probability of episodic mood disorder comorbidity (CC = 55.87%, AA = 39.52%, LT = 41.84%, AS = 47.66%, P value < 0.001) and the highest probability of schizophrenia comorbidity (CC = 10.47%, AA = 20.84%, LT = 8.00%, AS = 10.49%, P value < 0.001). Conclusions: SIH admission rates as well as the gap between different racial groups have remained steady during the study period which can raise concerns about the effectiveness of programs aimed at decreasing SIH admission rates and/or reducing interracial disparity.